Information technology law : the law and society / Andrew Murray. - Murray, Andrew, 1972- (Oxford University Press, 2023)
'Information Technology Law' examines how law interacts with our actions in cyberspace and other elements of the information society. It considers the relationship between the legal system and the information society, covers issues such as governance, free expression and crime, and looks forward to future challenges.